Analysis of Bacterial Community Characteristics, Abundance of Antibiotics and Antibiotic Resistance Genes Along a Pollution Gradient of Ba River in Xi’an, China - Guan, Yongjing; Jia, Jia; Wu, Lang; Xue, Xue; Zhang, Guo; Wang, Zaizhao (Frontiers in Microbiology, 2018)
The microbial communities in freshwater have raised concerns about the ecosystem and human health. Many ecological environmental problems have been found in urban river because of the unreasonable use and long-term wastewater discharge. In this study, we explored the bacterial community composition, abundance of 14 antibiotics and 21 antibiotic resistance genes (ARGs), and water environment features in 7 water samples and 7 sediment samples from Ba River in Xi’an, China. Results showed Proteobacteria and Bacteroidetes were the dominant phyla in all samples, and sediment samples had a higher bacterial diversity and richness than it in water. Bacterial communities of site 5 and 6 were clustered in discrepant patterns compared to those at remaining sites from other samples. It might be influenced by nutrients, heavy metals and antibiotics. Antibiotics concentrations ranged from 1.26 to 1.61 × 103 ng L-1 in water samples and 1.55 to 4.05× 102 μg kg-1 in sediment samples. Sulfamerazine (SM1) and erythromycin (ERY) were the chief antibiotics in water samples, while the level of oxytetracycline (OTC) and cefazolin (CFZ) were higher in sediment samples. Canonical correspondence analysis showed that trimethoprim (TMP) was significantly related to Acinetobacter in W6, and that SM1 and OTC had positive correlation with Arcobacter in W5. The tetC, blaTEM, ermF and sul1 had higher pollution abundance ranging from 10-4 to 100 copies/16S rRNA gene copies in all samples. Significant correlations were observed between ARGs and matching antibiotics, suggesting that antibiotics can pose the selective pressure on ARGs in this river. In summary, these finding might provide some new data to the limited information available on the bacterial community characteristics, abundance of antibiotics and ARGs in urban river of China.